Does the analysed size fraction of benthic foraminifera influence the ecological quality status and the interpretation of environmental conditions? Indications from two northern Norwegian fjords. (February 2022) - Klootwijk, Anouk T.; Alve, Elisabeth
Highlights: Fractions had the same or similar H'log2, ES100 and NQI Ecological Quality Status. AMBI most affected by analysed size fraction with a moderate EcoQS at one location. Some species holding ecological information did not occur in the > 125 µm fraction. > 125 µm fraction mostly sufficient to establish the EcoQS in unpolluted fjords. Abstract: The introduction of the European Water Framework Directive has increased the interest in benthic foraminifera as a biomonitoring tool. This prompted the need to standardise the methods used to analyse benthic foraminifera, including which sediment fraction to analyse. In some regions benthic foraminifera produce small (< 125 µm) adult tests, and the current study assessed the effect of analysing the > 63 µm or > 125 µm fraction on determining the Ecological Quality Status (EcoQS) in two fjords in northern Norway. The diversity indices Shannon-Wiener index (H'log2 ) and Hurlbert's rarefaction index (ES100 ), and the multi-metric Norwegian Quality Index (NQI), from both the > 63 µm and > 125 µm fraction resulted in the same or similar EcoQS, reflecting good environmental conditions in both fjords. The same applied to the AZTI's Marine Biological Index (AMBI), except at one location which had moderate EcoQS. At this location especially, more foraminifera with a tolerant or opportunistic response to organic matter enrichment occurred in the > 63 µm fraction than in the > 125 µm fraction. Hence, the higher H'log2 and ES100 of the > 63 µm fraction can be somewhat misleading as it indicates better environmental conditions, whereas the AMBI indicates more organic matter input. The Stainforthia group and Epistominella vitrea, indicating organic matter enrichment and increased primary productivity were, however, mostly absent in the > 125 µm fraction. Their absence in this fraction could have consequences for monitoring potential anthropogenic pressure factors and identifying long-term changes in environmental conditions when using this fraction. This study suggests the > 125 µm would be mostly sufficient for determining the EcoQS in northern Norway.